The prevalence and significance of a short QT interval in 18 825 low-risk individuals including athletes. Issue 2 (23rd September 2015) - Dhutia, Harshil; Malhotra, Aneil; Parpia, Sameer; Gabus, Vincent; Finocchiaro, Gherardo; Mellor, Greg; Merghani, Ahmed; Millar, Lynne; Narain, Rajay; Sheikh, Nabeel; Behr, Elijah R; Papadakis, Michael; et al.
Abstract : Objectives: The short QT syndrome is a cardiac channelopathy characterised by accelerated repolarisation which manifests as a short QT interval on the ECG. The definition of a short QT interval is debated, ranging from <390 to ≤320 ms, and its clinical significance in healthy young individuals is unknown. We assessed the prevalence and medium-term significance of an isolated short QT interval in a diverse young British population. Methods: Between 2005 and 2013, 18 825 apparently healthy people aged 14–35 years underwent cardiovascular evaluation with history, physical examination and ECG. QT intervals were measured by cardiologists using 4 recommended guidelines (Seattle 2013, Heart Rhythm Society 2013, European Society of Cardiology 2010 and American Heart Association 2009). Results: The prevalence of a short QT interval was 0.1% (26 patients, ≤320 ms), 0.2% (44 patients, ≤330 ms), 7.9% (1478 patients, <380 ms), 15.8% (2973 patients, <390 ms). Male gender and Afro-Caribbean ethnicity had the strongest association with short QT intervals. Athletes had shorter QT intervals than non-athletes but athletic status did not predict short QT intervals. Individuals with short QT intervals ≤320 ms did not report syncope or a sinister family history, and during a follow-up period of 5.3±1.2 years, there were no deaths in this group. Conclusions: The prevalence of a short QT interval depends on the recommended cut-off value. Even at values ≤320 ms, there was an excellent medium-term prognosis among 14 people followed. We conclude that a definition of ≤320 ms is realistic to prevent overdiagnosis and excessive investigations.